2012
DOI: 10.1080/0028825x.2011.642887
|View full text |Cite
|
Sign up to set email alerts
|

Schizymenia dubyi(Rhodophyta, Schizymeniaceae), a new introduced species in Argentina

Abstract: Schizymenia dubyi (Chauvin ex Duby) J. Agardh is a red alga of the order Nemastomatales that is native to Europe, Asia and Oceania. The first specimen of this seaweed from the Argentinian coast was collected in the Chapadmalal intertidal wave-cut platform (38812?S, 57840?W) in September 2008. Taxonomic identification of the species was made on the basis of vegetative and reproductive characters and confirmed by DNA sequence analysis of the rbcL gene. The S. dubyi samples collected in the field were represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…), and S. dubyi has also been found on the Atlantic coast of Argentina (Ramirez et al. ). In some cases, they are thought to have been recently introduced (Ramirez et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…), and S. dubyi has also been found on the Atlantic coast of Argentina (Ramirez et al. ). In some cases, they are thought to have been recently introduced (Ramirez et al.…”
Section: Discussionmentioning
confidence: 96%
“…In some cases, they are thought to have been recently introduced (Ramirez et al. , D'Archino and Zuccarello ).…”
Section: Discussionmentioning
confidence: 99%
“…This section is also characterised by the highest proportions of 13-methoxyheneicosanoic (13MeO21:0), which is rare in lacustrine ecosystems. This methoxy acid has been identified in the red alga Schizymenia dubyi (Barnathan et al, 1998) in the Mediterranean and waters of Japan and Australia but has never been reported from lacustrine ecosystems (Ramirez et al, 2012). Kerger et al (1986) identified a series of methoxy acids (10MeO18:0, 11MeO18:0, 12MeO20:0, 13MeO20:0) and interpreted them as biomarkers from sulphur bacteria (Thiobacillus spp.).…”
Section: Inferred Paleoenvironment From Lipid Assemblagesmentioning
confidence: 99%
“…pers. ), especie nativa del hemisferio norte, introducida recientemente en Mar del Plata, Argentina (Ramírez et al, 2012), y que probablemente habría sido introducida con anterioridad a la costa chilena. En adelante se hará mención a esta especie como S. dubyi.…”
Section: Listado De Especies De Macroalgas Exóticas A) Depuración De unclassified
“…1e) es una especie nativa de la costa del Pacífico Norte, que en Chile muestra una distribución altamente disjunta, siendo reportada para Valparaíso, Navidad y Punta Arenas (Ramírez & Rojas, 1988;Ramírez & Santelices, 1991;Hoffmann & Santelices, 1997). Habita en pozas intermareales poco profundas en sectores muy expuestos al oleaje (Ramírez & Rojas, 1988), y a nivel mundial ha sido recientemente introducida en Argentina (Ramírez et al, 2012). 7.…”
Section: Listado De Especies De Macroalgas Exóticas A) Depuración De unclassified